PENGARUH KAPABILITAS JEJARING USAHA DAN MEDIA SOSIAL TERHADAP KINERJA USAHA - Zulfikar, Rizki; Novianti, Lastri (JURISMA : Jurnal Riset Bisnis & Manajemen, 2018)
Bandung is a city with a sizable industrial fabric. One of fabrics industry that is Cigondewah Sentra fabrics Bandung, after decades of operation and get the title as the longest fabric sales market in Bandung. The number of entrepreneurs engaged in textile creating a very tight competition among businesses, therefore the necessary attention to the capabilities of Business Networking and Social Media that can improve business performance. This study aims to examine the effects of business networking capabilities and social media have on business performance. â€œThe method used in this research is descriptive analysis and verification.â€ In purposive sampling. While collecting the data, the technique used is through interviews and questionnaires. The analysis used in this research is multiple regression analysis. These results indicate the ability of business networking and social media influence on business performance. Variable social media into variables that have the greatest influence than the variable effort capabilities, namely the social media variables that are in both categories while variable business networking capabilities in a category quite well. Keyword: Business Network Capabilities, Social Media, Business Performance